Dose-Dependent Mild Kidney Injury Induced by Ethanol Extract of Rhodomyrtus tomentosa in Female Rats - Ekaputri, Tia Wida; Andani, Firstasya; Enis, Rina Nofri; Tarawifa, Susan; Puspasari, Anggelia; Maharani, Citra; Utami, Erisca Ayu (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2026)
Background: Rhodomyrtus tomentosa is widely used in traditional medicine, but its subchronic renal safety profile remains insufficiently explored. This study aimed to assess mild kidney injury induced by R. tomentosa leaf ethanol extract through qualitative and quantitative histopathological evaluation in female Rattus norvegicus. Methods: Twenty-four female rats were divided into six groups: a control and five treatment groups receiving the extract at doses of 200, 400, 800, 1600, and 3200 mg/kgBW for 14 days. Kidney tissues were evaluated via hematoxylin-eosin staining and image-based digital quantification across five fields of view per specimen to determine glomerular and tubular damage. Results: Qualitative evaluation revealed dose-dependent alterations, transitioning from mild glomerular hypercellularity at lower doses to focal necrosis and hemorrhage at higher doses. Quantitative analysis clarified a distinct compartmental vulnerability. Glomerular damage showed a descriptive upward trend across doses (9.75% to 13.53%) but lacked statistical significance (Kruskal-Wallis, p = 0.05). Conversely, tubular damage increased sharply from 1.99% to 17.49%, demonstrating a highly significant dose-dependent escalation (p = 0.001). Post-hoc pairwise comparisons confirmed that significant tubular degeneration manifested critically at elevated exposures of 1600 mg/kgBW (p = 0.014) and 3200 mg/kgBW (p = 0.002) compared to the control group. Conclusion: The ethanol extract of R. tomentosa leaves induces dose-dependent renal alterations, with tubular structures exhibiting significantly higher susceptibility than glomeruli due to active metabolic clearance. However, the absolute tissue damage remains strictly within the mild, non-destructive category, establishing a reassuring safety margin for its pharmaceutical development.